EVALUACIÓN DE MOLÉCULAS COMERCIALES DE EFECTO FUNGICIDA AL CONTROL DE (Phytophthora palmivora) A NIVEL in vitro Y EN MAZORCAS DE (Theobroma cacao L.) - Bustamante Valverde, Magno Antonio (2023)
The crop yield of Theobroma cacao L. is mainly affected by the attack of diseases among the main Phytophthora palmivora, due to the limited existence of effective fungicides for its control. The present research was carried out in the Microbiology and Molecular Biology laboratory of the “UTEQ”. The objective is to evaluate commercial molecules with a fungicidal effect to control Phytophthora palmivora in vitro and in vivo. A completely randomized design (DCA) was used with an ADEVA and a 95% Tukey test.